Association of chronic inflammation and accelerated atherosclerosis among an indigenous black population with chronic kidney disease. - Muzamil Olamide Hassan; Therese Dix-Peek; Raquel Duarte; Caroline Dickens; Sagren Naidoo; Ahmed Vachiat; Sacha Grinter; Pravin Manga; Saraladevi Naicker (PLoS ONE)
Introduction Inflammation plays a major role in the development of atherosclerosis and cardiovascular morbidity and mortality in chronic kidney disease (CKD) patients. Toll-like receptor-4 (TLR4) is a major receptor for lipopolysaccharides (endotoxin) and other ligands involved in the pathogenesis of inflammation. We determined whether endotoxin levels and the presence of TLR4 polymorphisms are associated with markers of inflammation and atherosclerosis among South African CKD patients. Materials and methods Endotoxin, lipopolysaccharide binding protein (LBP), serum CD14 (sCD14), interleukin-8 (IL-8), monocyte chemoattractant protein-1 (MCP-1) and carotid intima media thickness (CIMT) were measured in 160 participants (120 CKD patients and 40 controls). Associations between endotoxins and CIMT in the presence of sCD14, IL-8 and MCP-1, were assessed using odds ratios. Participants were screened for the presence of Asp299Gly and Thr399Ile TLR4 polymorphisms, and CIMT and inflammatory markers were compared between subjects with and without TLR4 polymorphisms. Results Endotoxin levels correlated with sCD14 (r = 0.441, p<0.001) and MCP-1 (r = 0.388, p<0.001) levels while increased CIMT was associated with MCP-1 (r = 0.448, p<0.001), sCD14 levels (r = 0.476, p<0.001), LBP (r = 0.340, p<0.001), and IL-8 (r = 0.395, p<0.001). Atherosclerosis was associated with endotoxin levels (odds ratio: 4.95; 95% confidence interval: 2.52-9.73; p<0.001), and was predicted by higher serum levels of inflammatory markers. Analysis of patients with TLR4 polymorphisms showed reduced serum levels of inflammatory markers and CIMT values compared with the patients carrying the wild type TLR4 alleles. Conclusion The study demonstrated associations between circulating endotoxaemia, systemic inflammation and accelerated atherosclerosis among South African CKD patients, and showed that the atherogenic predictive power of endotoxaemia was significantly increased by the presence of elevated levels of inflammatory markers. Additional findings, which must be confirmed, suggest that TLR4 polymorphisms are associated with low levels of inflammatory markers and CIMT values.